Penilaian Manfaat Nilai Ekonomi Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat - Septiani, Yustirania; Jalunggono, Gentur (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2020)
The Community-Based Drinking Water Provision Program (Pamsimas) is a government program that collaborates with regions and is supported by the World Bank in terms of increasing access to drinking water, sanitation, and improving health, especially in solving diarrhea and water-borne and environmental diseases. This program requires a large budget so it is a shame if it does not have a positive impact on society. So it isnecessary to study the impact of different programs for the community and information on the effectiveness of the program so that apart from being useful, the community can jointly contribute to the sustainability of the program. The method used is the binomial test related to differences in the level of clean water availability before and after the Pamsimas program. The ratio of effectiveness to see the relationship between output and the expected end result. The greater the output contribution to the achievement of the final result, it can be said that the organization, program or activity is effective. The results showed that there were differences in the availability of clean water facilities in Sudimara Village, Cilongok District, Banyumas Regency, Central Java before and after the Pamsimas program. Meanwhile, based on 6 indicators of success, it shows the level of effectiveness, only the fifth criterion is in the effective criteria and the other 5 indicators are in the very effective criteria. The conclusion of the Pamsimas program has been optimal and successful in providing clean water and this program is also said to be very effective in its implementation in Sudimara Village, Cilongok District, Banyumas Regency, Central Java. Abstrak Program Penyediaan Air Minum Berbasis Masyarakat (Pamsimas) adalah program pemerintah yang bekerjasama dengan daerah didukung Bank Dunia untuk peningkatan akses layanan air minum, sanitasi, dan peningkatan kesehatan terutama dalam penyelesaian penyakit diare dan penyakit yang ditularkan melalui air dan lingkungan. Program ini membutuhkan anggaran yang besar sehingga disayangkan jika tidak membawa dampak yang positif pada masyarakat. Sehingga perlu adanya kajian mengenai dampak perbedaan program bagi masyarakat dan informasi mengenai efektifitas keberadaan program agar selain bermanfaat, masyarakat diminta bersama-sama berkontribusi demi keberlanjutan program.. Metode yang digunakan yakni uji Beda terkait perbedaan tingkat ketersediaan air bersih sebelum dan sesudah adanya program pamsima. Rasio Efektivitas untuk melihat hubungan diantara output dan hasil akhir yang diharapkan. Semakin besar kontribusi output pada pencapaian hasil akhir, dapat dikatakan bahwa organisasi, program, atau kegiatan tersebut efektif. Hasil penelitian memperlihatkan terdapat perbedaan ketersediaan sarana air bersih di Desa Sudimara sebelum dan setelah adanya program Pamsimas. Sedangkan berdasarkan 6 indikator keberhasilan memperlihatkan tingkat efektivitasnya sangat efektif dan efektif. Simpulan program pamsimas sudah optimal dan berhasil dalam penyediaan air bersih di Desa Sudimara. Program ini juga sudah dapat dikatakan efektif dalam pelaksanaan. Kata Kunci : Uji Binomial, Rasio Efektivitas, Pamsimas